Observations of Continuous Quasiperiodic Auroral Pulsations on Saturn in High Time‐Resolution UV Auroral Imagery. Issue 4 (3rd April 2019) - Bader, A.; Badman, S. V.; Yao, Z. H.; Kinrade, J.; Pryor, W. R.
Abstract: Saturn's aurora represents the ionospheric response to plasma processes occurring in the planet's entire magnetosphere. Short‐lived ∼1‐hr quasiperiodic high‐energy electron injections, frequently observed in in situ particle and radio measurements, should therefore entail an associated flashing auroral signature. This study uses high time‐resolution ultraviolet (UV) auroral imagery from the Cassini spacecraft to demonstrate the continuous occurrence of such flashes in Saturn's northern hemisphere and investigate their properties. We find that their recurrence periods of order 1 hr and preferential occurrence near dusk match well with previous observations of electron injections and related auroral hiss features. A large spread in UV auroral emission power, reaching more than 50% of the total auroral power, is observed independent of the flash locations. Based on an event observed both by the Hubble Space Telescope and the Cassini spacecraft, we propose that these auroral flashes are not associated with low‐frequency waves and instead directly caused by recurrent small‐scale magnetodisc reconnection on closed field lines. We suggest that such reconnection processes accelerate plasma planetward of the reconnection site toward the ionosphere inducing transient auroral spots while the magnetic field rapidly changes from a bent‐back to a more dipolar configuration. This manifests as a sawtooth‐shaped discontinuity observed in magnetic field data and indicates a release of magnetospheric energy through plasmoid release. Key Points: Continuous  1‐hr quasiperiodic flashes in Saturn's UV aurora are revealed in high time‐resolution Cassini UVIS imagery The auroral flash locations and periodicities match well to quasiperiodic signatures observed recently in Cassini electron and radio data Small‐scale magnetodisc reconnection predominantly occurring at dusk is suggested as a likely driver